Activin receptor‐like kinase5 inhibition suppresses mouse melanoma by ubiquitin degradation of Smad4, thereby derepressing eomesodermin in cytotoxic T lymphocytes. Issue 11 (11th October 2013) - Yoon, Jeong‐Hwan; Jung, Su Myung; Park, Seok Hee; Kato, Mitsuyasu; Yamashita, Tadashi; Lee, In‐Kyu; Sudo, Katsuko; Nakae, Susumu; Han, Jin Soo; Kim, Ok‐Hee; Oh, Byung‐Chul; Sumida, Takayuki; et al.
<x xml:space="preserve">Abstract</x> Varieties of transforming growth factor‐β (TGF‐β) antagonists have been developed to intervene with excessive TGF‐β signalling activity in cancer. Activin receptor‐like kinase5 (ALK5) inhibitors antagonize TGF‐β signalling by blocking TGF‐β receptor‐activated Smad (R‐Smad) phosphorylation. Here we report the novel mechanisms how ALK5 inhibitors exert a therapeutic effect on a mouse B16 melanoma model. Oral treatment with a novel ALK5 inhibitor, EW‐7197 (2.5 mg/kg daily) or a representative ALK5 inhibitor, LY‐2157299 (75 mg/kg bid) suppressed the progression of melanoma with enhanced cytotoxic T‐lymphocyte (CTL) responses. Notably, ALK5 inhibitors not only blocked R‐Smad phosphorylation, but also induced ubiquitin‐mediated degradation of the common Smad, Smad4 mainly in CD8+ T cells in melanoma‐bearing mice. Accordingly, T‐cell‐specific deletion of Smad4 was sufficient to suppress the progression of melanoma. We further identified eomesodermin (Eomes), the T‐box transcription factor regulating CTL functions, as a specific target repressed by TGF‐β via Smad4 and Smad3 in CD8+ T cells. Thus, ALK5 inhibition enhances anti‐melanoma CTL responses through ubiquitin‐mediated degradation of Smad4 in addition to the direct inhibitory effect on R‐Smad phosphorylation.